2019
DOI: 10.1182/blood.2019000040
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol trimer enhances gene delivery to hematopoietic stem cells by reducing antiviral restriction at endosomes

Abstract: Key Points The cyclic resveratrol trimer caraphenol A safely enhances lentiviral vector gene delivery to hematopoietic stem and progenitor cells. Caraphenol A decreases interferon-induced transmembrane protein-mediated restriction in an endosomal trafficking-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 85 publications
0
21
0
Order By: Relevance
“…Recently, scientists have discovered that caraphenol A, a trimer of resveratrol, plays a unique role in gene therapy, which has brought resveratrol back into the spotlight. Torbett et al found that caraphenol A safely enhanced the gene delivery efficiency from LVs (lentiviral vector) to the HSC (hematopoietic stem cell), also reducing the transmembrane protein-mediated restriction to making it easier for vectors to pass through, which is a possible way to improve the therapeutic effect of gene therapy [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, scientists have discovered that caraphenol A, a trimer of resveratrol, plays a unique role in gene therapy, which has brought resveratrol back into the spotlight. Torbett et al found that caraphenol A safely enhanced the gene delivery efficiency from LVs (lentiviral vector) to the HSC (hematopoietic stem cell), also reducing the transmembrane protein-mediated restriction to making it easier for vectors to pass through, which is a possible way to improve the therapeutic effect of gene therapy [19].…”
Section: Introductionmentioning
confidence: 99%
“… 32 IFITM3 has been investigated most and was recently identified as the main target to improve gene transfer into hematopoietic stem cells through the use of resveratrol as transduction enhancer. 33 , 34 , 35 Although our data certainly support this strategy also for T lymphocytes, they also suggest that not only intracellular localization of IFITMs but also subtle changes in their overall expression levels may determine whether a particular T cell becomes properly transduced. 35 …”
Section: Discussionmentioning
confidence: 52%
“…The diarrhea index formula given below of the four groups are given: Resveratrol have many antiviral properties and used against the Rotavirus diarrhea and enterovirus [39], which cause the inflammation of the hearts of mice, which reduced the hearts ability to pump he blood normally and blocked the replication of enterovirus [40]. Therefore, we use he resveratrol against the Rotavirus, which is harmful for the piglets [41], which cause diarrhea and gastroenteritis in piglets and we know that resveratrol dry suspension could regulate the immune response and inhibit the diarrhea and other viral infection [42].…”
Section: Diarrhea Indexmentioning
confidence: 99%